Ileal Atresia Mimicking Hirschsprung Disease on Contrast Study: A Case Report and Diagnostic Re-evaluation - Anisa Ika Pratiwi; Ibnu Sina Ibrohim (Open Access Indonesian Journal of Medical Reviews, 2025)
The differentiation between congenital causes of neonatal bowel obstruction, such as ileal atresia and Hirschsprung disease, is paramount for appropriate surgical planning. While clinically similar, their radiological findings can overlap, creating significant diagnostic challenges. Ileal atresia is a congenital anomaly characterized by the incomplete development of the ileum, resulting in intestinal obstruction. The aim of this study is to highlight the limitations of contrast studies in neonatal bowel obstruction and to reinforce the principle that in the face of discordant clinical and radiological evidence. We present the case of a full-term female neonate, born at 39 weeks of gestation, who developed symptoms of green vomiting and delayed bowel movements on her second day of life. An initial colon in loop contrast study at eight days of age was suggestive of short-segment Hirschsprung disease, showing a narrowed rectal lumen and a transition zone in the rectosigmoid region. However, due to persistent signs of distal bowel obstruction, surgical exploration was performed on the ninth day of life. Intraoperatively, the diagnosis was revised to Type 3A ileal atresia located 20 cm from the ileocecal junction, with significant adhesions. The management involved adhesiolysis, resection of the atretic ileal segment, and a primary ileo-ascending anastomosis. The postoperative course was complicated by hypovolemic shock and suspected sepsis neonatorum, which were managed successfully with intensive care support, including intravenous antibiotics and parenteral nutrition. The patient showed significant improvement by the fifth postoperative day and was discharged with normal gastrointestinal function. In conclusion, this case underscores a critical diagnostic pitfall where the 'microcolon of disuse' in distal ileal atresia radiologically mimicked the transition zone of Hirschsprung disease. It highlights that while contrast studies are invaluable, a high index of clinical suspicion and readiness for surgical exploration are essential for accurate diagnosis and timely intervention in complex cases of neonatal bowel obstruction.